Generation of Carbamoyl Radicals and 3,4-Dihydroquinolin-2(1H)-ones Enabled by Iron Photoredox Catalysis - Fu, Yanhua; Zhang, Chao; Cai, Tao; Feng, Gaofeng (Synlett, 2024)
A new protocol for accessing 3,4-dihydroquinolin-2(1H)-ones was established through a sequence of iron-catalyzed photoredox generation of carbamoyl radicals from oxamic acids, addition of the carbamoyl radicals to electron-deficient alkenes, intramolecular cyclization, and aromatization. The process is compatible with a variety of N-phenyloxamic acids and monosubstituted, 1,1-disubstituted, and trisubstituted electron-deficient alkenes. Employing cheap, readily available, and environmentally benign iron as the catalyst, the protocol provides an excellent alternative for synthesis of 3,4-dihydroquinolin-2(1H)-ones.
Keywords: iron catalysis; photoredox catalysis; dihydroquinolinones; carbamoyl radicals; oxamic acids